Update of the Brazilian consensus recommendations on Duchenne muscular dystrophy - Araujo, Alexandra Prufer de Queiroz Campos; Saute, Jonas Alex Morales; Fortes, Clarisse Pereira Dias Drumond; França Jr, Marcondes Cavalcante; Pereira, Jaqueline Almeida; Albuquerque, Marco Antonio Veloso de; Carvalho, Alzira Alves de Siqueira; Cavalcanti, Eduardo Boiteux Uchôa; Covaleski, Anna Paula Paranhos Miranda; Fagondes, Simone Chaves; Gurgel-Giannetti, Juliana; Gonçalves, Marcus Vinicius Magno; Martinez, Alberto Rolim Muro; Coimbra Neto, Antônio Rodrigues; Neves, Flavio Reis; Nucci, Anamarli; Nucera, Ana Paula Cassetta dos Santos; Pessoa, Andre Luis Santos; Rebel, Marcos Ferreira; Santos, Flavia Nardes dos; Scola, Rosana Herminia; Sobreira, Cláudia Ferreira da Rosa (Arquivos de Neuro-Psiquiatria, 2023)
In the last few decades, there have been considerable improvements in the diagnosis and care of Duchenne muscular dystrophy (DMD), the most common childhood muscular dystrophy. International guidelines have been published and recently reviewed. A group of Brazilian experts has developed a standard of care based on a literature review with evidence-based graded recommendations in a two-part publication. Implementing best practice management has helped change the natural history of this chronic progressive disorder, in which the life expectancy for children of the male sex in the past used to be very limited. Since the previous publication, diagnosis, steroid treatment, rehabilitation, and systemic care have gained more significant insights with new original work in certain fields. Furthermore, the development of new drugs is ongoing, and some interventions have been approved for use in certain countries. Therefore, we have identified the need to review the previous care recommendations for Brazilian patients with DMD. Our objective was to create an evidence-based document that is an update on our previous consensus on those topics.
Keywords: Muscular Dystrophy; Duchenne; Consensus; Practice Guideline; Diagnosis; Genetic Testing; Steroids; Rehabilitation; Drug Therapy; Standard of Care; Drug Development